Pemberdayaan Perempuan Melalui Pemanfaatkan Sumber Daya Lokal di Desa Rantau Puri Kecamatan Muara Bulian - Sri Harimurti; Rusnani Rusnani; Firna Varina; Enita Enita; Ratna Dewi (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
Empowerment of women through the use of local resources provides change and progress in Rantau Puri Village located in Muara Bulian District, Batang Hari Regency. Local resources as a dimension of local wisdom include Natural Resources (SDA), Human Resources (HR), and Socio-Cultural Resources that must be utilized to achieve change, progress and prosperity. Utilization of these three local resources in an integrated manner can provide independence. The kepok banana is one of the local natural resources developed by the local community, the kepok banana was chosen because it is often found in the local area. Banana kepok can be processed into chips with various flavors and also opaque, while for the heart of banana kepok you can make steak. Processing made from bananas is still done traditionally or manually so that the resulting product does not meet market demand. The purpose of this service is to provide assistance to the joint business group (KUBE) of Rantau Puri village through the use of local resources to be managed into regional superior products. The service will be held on October 2, 9 and 16, 2021. The methods used to achieve the objectives include: (a) socialization of the program to target groups, local government and communities (b) counseling on the use of local resources (c) skills training to target groups . The results of community service in the form of empowerment or assistance to women through the use of kepok bananas which are processed into banana chips, opaque and steak. The conclusion of this service is that there needs to be further assistance to the community to be wiser and skilled both in terms of skills and technology in the use of local resources.